A rare cause of bleeding gastric ulcer: multiple myeloma - Agarwal, Rakesh; Lahiri, Durjoy; Baid, Rashmi; Mukhopadhyay, Jotideb (International Journal of Research in Medical Sciences, 2017)
The causes of GI bleed are many and varied with peptic ulcers accounting for about 50% cases. Multiple myeloma is the most common lymphoid neoplasm in older adults and accounts for approximately 10% of all hematologic malignancies. Extraosseous manifestations are said to be present in less than 5% of patients with Multiple Myeloma with GI ulcers only being described rarely. In this report we describe a case of a 58 year old lady presenting with weakness, palpitations, gum bleeding with recent onset melena. She had severe anaemia with thrombocytopenia and markedly elevated ESR. An UGI endoscopy revealed a 1x0.5 cm ulcer infiltrated by lymphoplasmacytic cells and histiocytes with a few neutrophils. Serum globulin fraction was markedly high and Serum protein electrophoresis revealed it to be a case of multiple myeloma with Igʎ secreting monoclonal cells. Bone marrow aspirate revealed 40 % plasma cells with some binucleate and trinucleate forms. The patient was diagnosed as stage III multiple myeloma (International staging system) and treated with dexamethasone, zoledronic acid and thalidomide. Our case highlights a very atypical presentation of multiple myeloma and alerts the clinician to keep an eye of suspicion in dealing with peptic ulcer cases especially in the elderly.